Redox regulation of autophagy in Arabidopsis: The different ROS effects - Robert, German; Enet, Alejandro; Saavedra Borelli, Laura Lucia; Lascano, Hernan Ramiro (Elsevier, 2025)
Autophagy plays a key role in the responses to different stress condition in plants. Reactive oxygen species (ROS) are common modulators of stress responses, having both toxic and signaling functions. In this context, the relationship between ROS and autophagy regulation remains unclear, and in some aspects, contradictory. In this study, we employed pharmacological and genetic approaches to investigate the effects of different ROS on the cytoplastic redox state and autophagic flux in Arabidopsis thaliana. Our results demonstrated that oxidative treatments with H 2 O 2 and MV, which drastically increased the oxidized state of the cytoplasm, reduced the autophagic flux. Conversely, singlet oxygen, which did not have significant effects on the cytoplasmic redox state, increased the autophagic flux. Additionally, our findings indicated that after H 2 O 2 and high light treatments and during the recovery period, the cytoplasm returned to its reduced state, while autophagy was markedly induced. In summary, our study unveils the differential effects of ROS on the autophagic flux, establishing a correlation with the redox state of the cytoplasm. Moreover, it emphasizes the dynamic nature of autophagy in response to oxidative stress and the subsequent recovery period.